2020
DOI: 10.1111/nmo.13826
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment prevents chronic stress‐induced brain‐gut axis dysfunction through a GR‐mediated mechanism in the central nucleus of the amygdala

Abstract: The usefulness of psychotherapy, such as cognitive behavioral therapy (CBT) that encompasses cognitive and behavioral strategies that aim to improve the underlying thinking or behavioral patterns, extends far beyond the treatment of stress-related mood and psychological disorders such as anxiety and depression. 1-3 Nowadays, CBT is also being used to improve the quality of life in patients suffering from chronic pain, such as musculoskeletal pain, 4-6 pelvic pain, 7 and arthritic pain. 8 Clinical evidence sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…Long‐Evans rats were also used to investigate alterations in corticolimbic CRF signaling following stress exposure and/or linaclotide treatment based on previous studies showing adult stress induced significantly elevated HPA axis activity within this strain 31–33 . Importantly, the homotypic stressor employed during this study (water avoidance stress) induces comparable behavioral changes in Fischer 344 and Long‐Evans rats, with both strains exhibiting an increased fecal‐pellet output during the stress exposure and a subsequent increase in the visceromotor response to colorectal distension following the exposure 34–37 . Rats were double‐housed on Sani‐Chip bedding in standard individually ventilated cages at 23°C with a relative humidity of 50% on a 12‐hr light/dark cycle (7:00 a.m. to 7:00 p.m.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long‐Evans rats were also used to investigate alterations in corticolimbic CRF signaling following stress exposure and/or linaclotide treatment based on previous studies showing adult stress induced significantly elevated HPA axis activity within this strain 31–33 . Importantly, the homotypic stressor employed during this study (water avoidance stress) induces comparable behavioral changes in Fischer 344 and Long‐Evans rats, with both strains exhibiting an increased fecal‐pellet output during the stress exposure and a subsequent increase in the visceromotor response to colorectal distension following the exposure 34–37 . Rats were double‐housed on Sani‐Chip bedding in standard individually ventilated cages at 23°C with a relative humidity of 50% on a 12‐hr light/dark cycle (7:00 a.m. to 7:00 p.m.).…”
Section: Methodsmentioning
confidence: 99%
“…[31][32][33] Importantly, the homotypic stressor employed during this study (water avoidance stress) induces comparable behavioral changes in Fischer 344 and Long-Evans rats, with both strains exhibiting an increased fecal-pellet output during the stress exposure and a subsequent increase in the visceromotor response to colorectal distension following the exposure. [34][35][36][37] Rats were double-housed on Sani-Chip bedding in standard individually ventilated cages at 23°C with a relative humidity of 50% on a 12-hr light/dark cycle (7:00 a.m. to 7:00 p.m.). Food (5053 Irradiated PicoLab Rodent Diet; LabDiet) and water were available ad libitum.…”
Section: Animalsmentioning
confidence: 99%
“…Adult stress and anxiety models of IBS use physical stimuli [restraint stress ( 29 , 30 ), cold exposure ( 31 ), and forced swim test ( 32 )] and psychological stimuli such as water avoidance stress (WAS) ( 27 , 33 ) to induce visceral hypersensitivity. Chronic WAS specifically has been shown to decrease GR expression and increase CRH expression in the central nucleus of the amygdala (CeA) which induces visceral hypersensitivity that persists long after the stressor has been removed ( 20 , 27 , 34 ).…”
Section: Visceral Pain In Ibsmentioning
confidence: 99%
“…Moreover, the fact that the underlying mechanisms of CBT remain poorly understood continues to hinder the use of CBT to treat visceral pain. To unravel the underlying mechanisms of CBT, we and others have employed a rodent model of environmental enrichment (EE), the animal analog of CBT ( 20 ). In this review, we discuss the clinical presentation of chronic visceral pain, focusing on IBS.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that neonatal maternal deprivation (NMD) followed by adult multiple stress (AMS) advances the occurrence of visceral hypersensitivity in rats, partly due to enhanced norepinephrine (NE)-b 2 adrenergic signaling, while NMD alone does not cause visceral hyperalgesia at the age of 6 weeks [17]. The adrenergic signaling pathway plays an important role in regulating stress responses in many organs including the nervous system [18][19][20]. It has been reported that the activation of adrenergic receptors regulates the transmission of nociceptive information by inhibiting neurons and neurotransmitter release [15].…”
Section: Introductionmentioning
confidence: 99%